Factor Models and Long-tern Underperformance of the IPOs - Iraj Asghari; Javad Shekarkhah; Mohammad Javad Salimi; Mohammad Marfu (راهبرد مدیریت مالی, 2024)
IntroductionAccording to the research literature of initial public offerings (IPOs), despite the high Performance of them in the short-term, their long-term performance will probably be lower than the average performance of the relevant market {or industry} and this issue, if confirmed, requires the special attention of capital market activists. By using factor models, the current research has focused on the long-term performance of IPOs and, accordingly, the phenomenon of their underperformance in the long-term. In particular, in order to create a broad and reliable insight into the phenomenon " long-term underperformance of IPOs”, analyzes have been carried out at various levels, including the market and industry levels.MATERIALS AND METHODS The research was conducted on 235 initial public offerings (IPOs) between February 2015 and December 2020 (57 months in total). The analyzes have been done with the approach of factor models and the use of monthly time series of portfolios consisting of initial public offerings (IPOs). To investigate the phenomenon of low or high Performance of IPOs, the intercept level of the models has been used. Due to the lack of agreement among researchers regarding the length of the long-term period of IPOs, this research has used three periods (12-24 and 36 months).Also, according to the existence of the different models explaining performance of the IPOs and the possible effects of the model on the results, three different and conventional models have been used, including Fama and French (2003 and 2015) and Hou et al.'s model (2015).The stock and over-the-counter markets have been investigated separately, and since the research data only made possible the portfolio of 4 chemical, pharmaceutical, agricultural, and basic metal industries, the analysis of industries was carried out only at the level of these 4 industries.RESULTS AND DISCUSSIONValidation test of the models supported their validity and the results of fitting them showed that all the investigated models have adequate explanatory power and the minimum adjusted explanatory power (adj R2) is 69% and the maximum is 85%. As the definition of the long-term period becomes longer, their explanatory power decreases. IPOs move almost in line with the market, and the most important factor in predicting their return is market risk and profitability, and other factors have little effect on explaining the long-term return of IPOs. Regarding the investigation of the under-performance phenomenon, it should be said that sufficient evidence was not obtained to support the phenomenon of low or high performance of initial public offerings. And the intercept of the models in all periods and for all models lacked statistical significance. Breaking the data into the market and industries level did not create a special difference in the results. The analysis of the 4 mentioned industries showed the phenomenon is not statestically significant in any of the industries, although in the case of the chemical industry, a borderline significance level with a positive coefficient was obtained in some periods. Whether the IPOs are listed in stock market or over-the-counter (OTC), does not make a difference in their long-term performance.CONCLUSIONThe evidence of the current research does not support the existence of the phenomenon of “IPOs long-term underperformance” its reverse form (over- performance) in any of the tested cases, and the results for periods of more than one year (12-24 and 36 months) and for both stock and over-the-counter (OTC) markets and for all four industries (, chemical, pharmaceutical, agriculture and basic metals), are consistent and the model used, also has no effect on it so it must be said that the existence of under or over-performance of IPOs in Iran's financial markets is not confirmed. In more technical terms, in periods of more than one year, the market does not recognize the difference between the IPOS and the other companies due to factors other than known fundamental factors. This issue challenges the need to adjust individual decision-making models in the face of initial public offerings, and on the other hand, provides guidelines for use by legislators when legislating processes related to the capital market and especially initial offerings